2.7k views
3 votes
Y+9÷2=y-3÷4-(y/3)
pls help​

2 Answers

3 votes

Answer:

y = -
(63)/(4) or - 15.75

Explanation:

Order of operations.

y +
(9)/(2) = y -
(3)/(4) -
(y)/(3) Subtract y from each side.

y - y +
(9)/(2) = y - y -
(3)/(4) -
(y)/(3)


(9)/(2) = -
(3)/(4) -
(y)/(3) Add
(3)/(4) to each side


(9)/(2) +
(3)/(4) = -
(3)/(4) +
(3)/(4) -
(y)/(3)


(9)/(2) +
(3)/(4) = -
(y)/(3) Find the common denominator for
(9)/(2) and
(3)/(4), which is 4


(9)/(2) *
(2)/(2) +
(3)/(4) = -
(y)/(3)


(18)/(4) +
(3)/(4) = -
(y)/(3)


(21)/(4) = -
(y)/(3) Multiply each side by 3


(21)/(4) * 3 = -
(y)/(3) * 3


(63)/(4) = - y Divide each side by -1

y = -
(63)/(4) = - 15
(3)/(4)

y = - 15.75

User Abhinav Gujjar
by
5.9k points
4 votes

Explanation:

There are 2 scenarios below. One without parenthesis and the second with. I believe the second one is your question.

  • y+9÷2=y-3÷4-(y/3)
  • y - y + y/3 = - 3/4 - 9/2 ⇒ combining like terms
  • y/3 = -3/4 - 18/4
  • y/3 = -21/4
  • y = -21/4*3
  • y = -63/4
  • y = - 15 3/4

===============

  • (y+9)÷2=(y-3)÷4-(y/3)
  • 12*(y+9)/2 = 12* (y-3)/4 - 12*y/3 ⇒ this is to get rid of fraction
  • 6(y+9) = 3(y-3) - 4y
  • 6y + 54 = 3y - 9 - 4y
  • 6y + 54 = - y - 9
  • 6y + y = - 9 - 54
  • 7y = - 63
  • 7y/7 = -63/7
  • y = -9
User Yuyang He
by
5.6k points